'The French Who Don't Go to the Movies': Government and Industry Assess the Audience, 1948–54. Issue 1 (1st October 2015) - Smoodin, Eric
Abstract : Who were the French who wouldn't go to movies? The question was a vexing one in France after the Second World War, to which the film industry and the national government sought answers. In 1948 the Gaumont Film Company commissioned a survey of who went to the movies, who didn't, and why. In 1954, the Centre National de la Cinématographie, acknowledging 'La crise du cinéma', published an ominously titled 'Inquest' about movies and the French public. Thus audience studies in France took on national importance, and created a sociological and psychological profile of viewers that could be used to enhance business practice and government policy.